Detection of Intrauterine Growth Retardation in 2nd And 3rd Trimester with Fetal Parameters and Umbilical Artery Doppler: Detection of Intrauterine Growth Retardation with Doppler - Saleem, Sidra; Kubra, Khadija Tul; Saleem, Zobia; Raza, Asim; Khan, Yasser; Rizwan, Areeba; Anwaar, Adeeba (Pakistan Journal of Health Sciences, 2025)
Intrauterine Growth Restriction (IUGR) occurs when a fetus fails to reach its growth potential. Ultrasound plays a key role in diagnosis by assessing fetal biometry, and estimated weight. Umbilical artery Doppler studies evaluate placental function, with abnormal findings like increased resistance or absent/reversed end-diastolic flow. Objective: To detect Intrauterine growth retardation in 2nd and 3rd trimester with fetal parameters and umbilical artery doppler. Methods: This descriptive cross-sectional research took place at Diagnostic centre, Combined Military Hospital, Lahore from September to December 2024. All eligible 130 females in 2nd and 3rd trimester had recruited excluding females with Polyhydromnias. The examination involved the use of a curvilinear transducer (3-5MHz). Non probability convenient technique was employed for data collection. IBM (SPSS) version 26.0 was used for data analysis. For inferential statistics, Chi square test was employed. Statistical p-value <0.05 was considered as a significant value. Results: The study involved 130 pregnant women (mean age 28.82 ± 4.64), with 29.2% in the 2nd and 70.8% in the 3rd trimester. IUGR history (25.4%), gestational hypertension (50.8%), and diabetes (19.2%) were noted. IUGR was diagnosed in 52 cases with 3–6week growth delays. Abnormal PI values in all cases confirmed PI as a reliable marker. Conclusions: In conclusion, fetal biometric parameters (BPD, HC, AC, FL) below the 10th percentile indicated IUGR in over one-third of 2nd and 3rd trimester pregnancies, with growth lags of 15–43 days. Abnormal umbilical artery Doppler PI was present in all IUGR cases, highlighting PI as a consistent and reliable detection marker.